Diagnostic performance of a stepwise cytological algorithm for biliary malignancy in primary sclerosing cholangitis. (2nd December 2018) - von Seth, Erik; Ouchterlony, Helena; Dobra, Katalin; Hjerpe, Anders; Arnelo, Urban; Haas, Stephan; Bergquist, Annika
Abstract: Background and aims: Detection of early cholangiocarcinoma (CCA) in primary sclerosing cholangitis (PSC) is challenging. The aim of this study was to evaluate the diagnostic accuracy of a stepwise approach to biliary brush cytology with sequential use of fluorescence in‐situ hybridization (FISH) for the detection of biliary malignancy in PSC. Method: We retrospectively studied consecutive patients with PSC who underwent biliary brushings at Karolinska University Hospital between 2009 and 2015 (n = 208). Brush samples were categorized as benign, equivocal (atypical or suspicious) and malignant. Equivocal cases were further analysed with FISH. Samples with a malignant cytology or positive FISH were considered positive. The diagnosis was determined after 12 months of follow‐up. Results: The diagnosis CCA was confirmed in 15 patients (7%), high‐grade dysplasia in three patients, and low‐grade dysplasia in five patients at follow‐up. Using the diagnostic algorithm, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) for a diagnosis of CCA were 80% (95%CI 52%‐96%), 96% (95%CI 92%‐98%), 60% (95%CI 36%‐81%) and 98% (95% CI 95%‐100%). In patients with equivocal cytology (n = 61), the sensitivity for CCA diagnosis increased to 100% (95%CI 72%‐100%) with a lower PPV of 58% (95%CI 34%‐78%). The diagnostic accuracy for detection of CCA in all patients was 95% (95%CI 91%‐97%). Conclusion: Biliary brush cytology with sequential use of FISH in equivocal cases seems to be a highly predictive diagnostic test for CCA in PSC. These results support the use of FISH when cytology is equivocal for detection of biliary malignancy in PSC.